Desenvolvimento de circuito pré-amplificador rápido sensitivo à carga para detecção de radiação Gama - Jose Carlos da Cunha (2009)
This paper proposes to review the contribution of electronics for analysis and pplication of nuclear physics phenomena, emphasizing the recovery and reconfiguration of spectrometers differential range of great quality, but degraded due to obsolescence of their electronic circuits. Practical effect is shown for the main methods of measurement of radiation energy by spectrometry, and measurement of position to obtain the image. The nuclear imaging methods are compared with conventional methods of analysis of pulse height, looking up face, among other information, (a) resolution in energy, (b) spatial resolution and (c) the signal noise that each method provides. Techniques are discussed for obtaining the histogram of amplitudes of determining the position of interaction and signal format. With the use of simplified hardware and data acquisition based on the logical device A-101 of Ampetek, this dissertation presents a project to implement the pre-amplifier connected to a digital set crystal scintillate detector containing sodium iodide doped with thallium, favoring chain electronics for the detection of gamma radiation formed by circuit pre-amplifier and discriminator output pulses ordered. The data acquisition is performed in an ordinary personal computer. The goal of this dissertation is to present all the steps necessary for the development of pre-digital amplifier and includes literature, study of equipment, and assembly of electronic circuit, data acquisition in real-time and presentation of results.